A mudança nas ciências segundo Paul Feyerabend - Tiago Luis Teixeira de Oliveira (2011)
This work is a general exposition of the Austrian philosophy of science Paul Feyerabend (1924-1994) regarding the problem of scientific change. Feyerabend's thought develops into methodological and epistemological discussions marked by a dispute between logical positivism and critical rationalism. Contention that sees the new historicist element emerging whose introduction, among others, was due to Thomas Kuhn and Paul Feyerabend. We organize our text to address the feyerabendian criticism of the empiricist model of theoretical change, namely the logic of reduction (Nagel) and explanation (Hempel and Oppenheim). In our first chapter we show the Feyerabend's rejection of the idea of neutrality of the observational language and the thesis of consistency and stability of the terms required, according to him, by the instrumentalist interpretation of theories. Our second chapter makes a similar path regarding to critical rationalism. The falsificationist model is shown insufficient for historical and methodological reasons. We discussed in our text the attribution of the "relativist deviation" to the historicist approach of the author. We present Feyerabend's opposition to the notion of verisimilitude. Against this idea, the philosopher states that a comparison of content ignores that a theoretical change can cause an ontological change. Our third chapter develops better the incipient ideas of our earlier chapters, in order to situate feyerabendian philosophy within his methodological option for realism. In this last chapter we discuss the hypothetical realism, incommensurability and his infamous theoretical anarchism, concluding on the possibility of a new rationality attentive to the themes introduced by the author.